Publication Metrics as a Tool for Measuring Research Productivity and Their Relation to Motivation - Alexander Kalgin; Olga Kalgina; Anna Lebedeva (Voprosy obrazovaniya / Educational Studies Moscow, 2019)
The article presents an analytical review of literature on publication metrics as a tool of performance management in academia. Issues of quantitative research assessment are investigated in the light of modern views of motivation, in particular through the lens of self-determination theory. The article provides an insight into empirical studies on the effects of intrinsic and extrinsic motivation on publication productivity, research quality and subjective wellbeing. Accumulated international experience in performance management is used as a basis for developing recommendations on how to improve academic governance.